Accounting for management : planning and control - Lynch, Richard M.; Williamson, Robert W. (New York : McGraw-Hill, 1983)
"Accounting for Management: Planning and Control was one of the first texts designed for general business majors, as well as accounting majors, to emphasize the usefulness of accounting information to management. This book retains the strengths and advantages of earlier editions and incorporates a number of significant changes. The main objective of this book continues to be that of earlier editions : to present to the college students, in an introductory manner, the usefulness of accounting for informing management decision in the realm of planning and control. The second objective- to sharpen the analytical and problem solving skill of the student- is placed in close conjunction with the first. In summary, this book stresses the two things : the acquisition on the part of the students of substantive knowledge pertaining to the management functions of planning and control, and the increase of their intellectual skill at problem analysis."
Includes index.
English text.
Keywords: Managerial accounting